LED Area Lighting to Reduce Glare for Roof Bolter Operators - Sammarco, John J. (Min Metall Explor, 2020)
Researchers from the National Institute for Occupational Safety and Health (NIOSH) developed a light-emitting diode (LED) area luminaire called the Saturn and conducted a laboratory study using a Fletcher High Dual-boom Mast Feed (HDDR) roof bolting machine. The Saturn luminaire was designed to (1) enhance floor illumination to enable better detection of trip hazards in the interior spaces of a roof bolter and (2) reduce glare that has typically been an issue of concern on roof bolters. This paper reports on the results of achieving the second objective. The existing roof bolter lighting was the baseline and was compared with three versions of the Saturn luminaire relative to light intensity (100%, 75%, and 50%). Discomfort and disability glare data were obtained from 30 participants that comprised three age groups. Discomfort glare perceptions were obtained using the De Boer rating scale, and disability glare was quantified by using Mars Letter Contrast Sensitivity tests. Discomfort glare was reduced at least 3 levels with all Saturn versions. Also, a predictive model was used to estimate discomfort glare, and the results were similar. Disability glare was the least for the Saturn’s 50% intensity, and all Saturn versions had significantly less disability glare than with the baseline lighting. Veiling luminance was calculated and used as another indicator of disability glare. Veiling luminance was 28 to 42 times greater with the baseline lighting as compared with that of the Saturn lighting. Lastly, visibility levels were calculated. The Saturn versions were 4 to 6.5 times better in terms of visibility level.